STRATEGI GURU MADRASAH MENINGKATKAN MUTU PEMBELAJARAN ERA DISRUPSI DI KEDIRI - Pristian, Dhendi; Hambali, Muh. (J-PAI: Jurnal Pendidikan Agama Islam, 2019)
Learning quality is the determinant of service in a madrasah. The teacher who has an educational position, instilling values that uphold civilization does not merely transfer knowledge from the teacher to students in the classroom. In this disruption era, artificial intelligence emerged which replaced the teacher's position in the matter of transferring knowledge. The condition of information technology innovation continues to experience rapid development in the era of industrial revolution 4.0. The impact is that teachers need mastery of pedagogy based on the use of strategies and online learning resources. The learning model must be carried out by madrasah teachers when they want qualified graduates, for this reason teachers are needed to be able to manage learning in the madrasah so that student and output inputs of students have relations with the challenges faced. . The objectives of this study are: First, describe and analyze the model of planning, implementation and strategy of madrasah teachers to improve the quality of graduates in MAN 1 and MAN 2 Kota Kediri. qualitative approach, as for the type of case study research with a multicase study design. Research Results in these two madrasah are: First, the concept of planning is a) making teamwork and choosing needs according to vision and mission, b) inviting teacher speakers who excel, c) designing meaningful learning that is short term, long term according to the vision, mission and goals madrasah, d) make a program and determine policy, e) check and revise the plan. Second, the steps of Implementation are: a) Commitment, b) teamwork, c) Communication, d) Implementation of programs is 1) improvement of the quality of mix-based subject teachers, 2) improving the quality of learning, 3) improving service quality and development curriculum, 4) improvement of academic and non-academic achievements.Keywords : Strategy; Teacher of Madrasah; Graduate Quality and Era disruption